Horizontal Forms of Chern Type on Complex Finsler Bundles - Ida, C. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
The aim of this paper is to construct horizontal Chern forms of a holomorphic vector bundle using complex Finsler structures. Also, some properties of these forms are studied.